Clinical Insights into the Homeopathic Treatment of SIADH-Induced Oliguria Using Apis Mellifica - Chanu, Khumukcham Julia; MK, Kamath; Rajachandra, G (Indian Journal of Integrative Medicine, 2025)
Oliguria, defined as urine output of less than 400 mL per day, occurs when excessive antidiuretic hormone (ADH) secretion in a syndrome of inappropriate antidiuretic hormone secretion (SIADH) leads to increased water reabsorption by the kidneys. This results in concentrated urine, reduced urine volume, and dilutional hyponatremia. If left untreated, it can cause electrolyte imbalances, fluid overload, acute kidney injury, and cardiovascular complications. Prompt intervention is essential to prevent kidney damage and other serious health outcomes. This case report discusses the management of an 81-year-old female with a history of hypertension, diabetes mellitus, SIADH, acute pulmonary thromboembolism, and chronic deep vein thrombosis. She presented with oliguria (100 mL in 24 hours) despite a fluid intake of 1430 mL via a nasogastric tube. Clinical features included altered sensorium, weakness, shortness of breath, mild fever (101.9°F), tachypnea (48 cpm), tachycardia (105 bpm), and bilateral lower limb edema. Investigations revealed serum urea of 50 mg/dL, creatinine of 1.0 mg/dL, hyponatremia (120 mEq/L), hyperkalaemia (5.7 mEq/L), hypochloremia (89 mEq/L), and a chest X-ray showing partial lung collapse. Following informed consent, a homeopathic treatment regimen with Apis mellifica 6 was initiated, based on the principles of individualized treatment and symptom totality. This remedy was prescribed to address the patient’s oliguria, dropsical condition, and respiratory distress. Within 48 hours, significant improvements were noted. Urine output increased, serum urea levels decreased, and breath sounds became audible up to 5th intercostal spaces. Additionally, the patient's sensorium improved, and respiratory distress was alleviated. This case highlights the potential efficacy of Apis mellifica in managing dropsical conditions, with improvements in both renal function and respiratory status, suggesting its role as a complementary treatment in palliative care.